MENINGKATKAN PELAYANAN PUBLIK PADA TATANAN OTONOMI DAERAH - Suherman (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2016)
Regional autonomy is a concept that can provide repair changes in the order of life in the community. There are some things that the purpose of the concept of local autonomy with respect to the change of the State structure centralized-hierarchical, to the State dezentralization politically, namely consolidation and support the process of democratization, impulse and motorcycle competition and rapid economic development, the reduction of urbanization, the fulfillment of social satisfaction, Cultural and religious affinity between the bureaucracy and the public, as well as the efficiency and effectiveness of public services. Public service is part of the activities that can be felt by the whole community in its survival. Services are basically a set of processes activities that take place regularly and continuously covering the whole of human life in society.